(untitled) (De Musica, 2021)
The aim of this article is to understand to what extent the ontological status of musical works has been affected by the advent of digital interfaces and the Internet. To this end, it examines some of the emerging phenomena often noted by researchers, such as remastering, the hybridization of genres, the dematerialization of media, and decontextualization. We note that although the “digital revolution” has not fundamentally changed the status of notated and oral works, it has had a significant impact on phonographic works. By addressing more distracted and short-lived forms of reception, these are presented as artefact-recordings conceived in a more open, interactive or modular way, able to incorporate an explicitly multimedia dimension.